Uncle Dick Wootton : the Pioneer Frontiersman of the Rocky Mountain Region. - Wootton, Richens (Narrative Press, the, 2004)
In this unsurpassed tale of adventure on the American frontier, "Uncle Dick" Wootton relates with steely calm dozens of escapades that a less daring man would not have survived. He remembers his life in incredible detail, and where his memory fails his talent for storytelling takes over. Either way we get an entertaining and historically significant narrative, spanning much of the 19th century.